Effect of water regime on the growth, flower yield, essential oil and proline contents of Calendula officinalis - SAMI ALI METWALLY; KHALID ALI KHALID; BEDOUR H. ABOU-LEILA (Nusantara Bioscience, 2013)
Abstract. Metwally SA, Khalid KA, Abou-Leila BH. 2013. Effect of water regime on the growth, flower yield, essential oil and proline contents of Calendula officinalis. Nusantara Bioscience 5: 65-69. The effects of water regime on the growth, content of essential oil and proline of Calendula officinalis L. plants were investigated. Water regimes of 75% of field water capacity increased certain growth characters [i.e. plant height (cm), leaf area (cm2), flower diameter (cm) and spike stem diameter] and vase life (day). Water regime promoted the accumulation of essential oil content and its main components as well as proline contents.